The Philosopher’s Hunt. Comments to Plato’s Sophist - Pino Posada, Juan Pablo (Estudios de Filosofía, 2006)
The following pasaje illustrates the theme of this paper: "Or perhaps, have we fallen inadvertently by Zeus in the science of free men and searching for the Sophist, not the risk of having found the philosopher first?" (253c3-IQ). The fact that the stranger from Elea surprisingly finds himself with the Philosopher in a conversation that pretends to offer a definition of the Sophist, makes one think how little unheeded the closeness between the "free man” and the imitador was for Plato, in the Sophist, the platonic interest is centered in evincing this closeness and, at the same time, in defining the boundaries among them, making the first a hunter of the second. The present paper explores the sense of the hunt attending the following singularities 1) the formal procedure that it follows, 2) the question that guides it; 3) the quality of spirit that asks; 4) the words with which the interlocutors name it; y 5) the “noble" game he finds at last